Measuring women’s empowerment in agriculture - International Food Policy Research Institute (International Food Policy Research Institute, 2016)
WEAI is the first comprehensive and standardized measure of women’s empowerment and inclusion in the agricultural sector. WEAI is being used in the monitoring and evaluation of USAID’s Feed the Future Initiative in 19 countries. As of August 2016, at least 57 external organizations had used the WEAI in 35 countries in Asia, Africa, and Latin America.